2015
DOI: 10.1371/journal.pone.0141393
|View full text |Cite
|
Sign up to set email alerts
|

A Single Bout of Moderate Aerobic Exercise Improves Motor Skill Acquisition

Abstract: Long-term exercise is associated with improved performance on a variety of cognitive tasks including attention, executive function, and long-term memory. Remarkably, recent studies have shown that even a single bout of aerobic exercise can lead to immediate improvements in declarative learning and memory, but less is known about the effect of exercise on motor learning. Here we sought to determine the effect of a single bout of moderate intensity aerobic exercise on motor skill learning. In experiment 1, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
158
2
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(188 citation statements)
references
References 43 publications
16
158
2
12
Order By: Relevance
“…Our results suggest that high intensity exercise did not provide a significant additional benefit to learning of a novel locomotor pattern, conflicting with the results of previous studies examining the effects of exercise on motor learning in neurologically intact adults (Roig et al, 2012; Skriver et al, 2014; Statton et al, 2015). While non-significant, there were trends toward differences between the groups (Figure 5).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that high intensity exercise did not provide a significant additional benefit to learning of a novel locomotor pattern, conflicting with the results of previous studies examining the effects of exercise on motor learning in neurologically intact adults (Roig et al, 2012; Skriver et al, 2014; Statton et al, 2015). While non-significant, there were trends toward differences between the groups (Figure 5).…”
Section: Discussioncontrasting
confidence: 99%
“…Converging evidence has linked exercise with improved cognitive function in healthy individuals as well as those post stroke (Colcombe & Kramer, 2003; Kluding, Tseng, & Billinger, 2011; Quaney et al, 2009; Rand, Eng, Liu-Ambrose, & Tawashy, 2010; Winter et al, 2007). Evidence citing the effects of aerobic exercise on motor learning, however, is sparse in comparison to studies of cognitive performance and learning (Roig, Skriver, Lundbye-Jensen, Kiens, & Nielsen, 2012; Skriver et al, 2014; Statton, Encarnacion, Celnik, & Bastian, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Roig et al (2012) demonstrated that 20 min of intense cycling performed immediately before or after practicing a visuomotor skill task improves retention of the motor skill more than practicing the task alone. This finding was further supported by Statton, Encarnacion, Celnik, and Bastian (2015) and Mang, Snow, Campbell, Ross, and Boyd (2014) who observed that 20–30 min of moderate aerobic exercise led to an immediate improvement in motor performance of a skilled task. It has been suggested that when exercise precedes practice, improvements in skill learning could be due to better encoding of procedural information whereas when exercise is performed after practice is perhaps due to consolidation of long-term memory.…”
Section: Aerobic Exercise As Primingsupporting
confidence: 55%
“…However, previous studies using procedural tasks have provided evidence that in those settings the close proximity of exercise maximizes its effects on memory [29][30][31] (for an exception, see [32]). For this reason, it seems that the effect of exercise on memory is not only modulated by timing but also by the type of memory investigated.…”
Section: Discussionmentioning
confidence: 99%